2014
DOI: 10.2500/aap.2014.35.3793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of angiopoietin 1 and 2, vascular endothelial growth factor, and tumor necrosis factor alpha levels in asthmatic children

Abstract: Asthma is characterized by chronic airway inflammation that is associated with structural changes termed airway remodeling. Recently, cytokines/mediators that augment inflammation have been attracting attention in this field. The aim of this study was to evaluate serum angiopoietin (Ang)-1, Ang-2, vascular endothelial growth factor (VEGF), and tumor necrosis factor (TNF) alpha values, which have important roles in inflammation, angiogenesis, and remodeling in asthmatic children. We also documented correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[25] IL-8 levels were increased in children who developed wheezing illnesses in response to rhinovirus [26] ; in another cohort, individuals who wheezed with rhinovirus were at additional risk of persistent wheezing at follow up at age 3 years. [27] Fetal exposure to inflammatory cytokines, including IL-6, IL-8, and TNF-α, is increased with chorioamnionitis and has been linked to chronic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…[25] IL-8 levels were increased in children who developed wheezing illnesses in response to rhinovirus [26] ; in another cohort, individuals who wheezed with rhinovirus were at additional risk of persistent wheezing at follow up at age 3 years. [27] Fetal exposure to inflammatory cytokines, including IL-6, IL-8, and TNF-α, is increased with chorioamnionitis and has been linked to chronic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study Angiopoietin-2 rather than Angiopoietin-1 was associated with asthma and Angiopoietin-1/Angiopoietin-2 ratio was positively correlated with lung function in adult asthma patients [ 16 ]. More recently, Angiopoietin-1 levels and Angiopoietin-1/Angiopoietin-2 ratio were shown to be reduced in children with asthma and no correlation of proangiogenic factors with respiratory function was found [ 23 ]. Interestingly, Angiopoietin-1 and Angiopoietin-2 levels were recently detected to be upregulated in the induced sputum from patients with optimally treated asthma, and seemed to be also related to the smoking status [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggest that serum Ang1 may stimulate MCps to enhance their migration across vascular ECs into inflamed tissues. However, this concept is controversial, because another study reported a decrease, rather than an increase, in the serum titer of Ang1 in asthmatic patients [ 45 ]. The expression of Ang2, another ligand of Tie2, had also been reported to increase in asthmatic lung [ 43 ].…”
Section: Discussionmentioning
confidence: 99%